Time-Dependent Distribution of Hydroxychloroquine in Cynomolgus Macaques Using Population Pharmacokinetic Modeling Method - Qi Liu; Qi Liu; Guofang Bi; Guiying Chen; Xuan Guo; Siqi Tu; Xiaolin Tong; Man Xu; Mengjie Liu; Bei Wang; Hongliang Jiang; Jufeng Wang; et al. (Frontiers Media S.A., 2021)
To evaluate the biodistribution of hydroxychloroquine (HCQ) in cynomolgus macaques and receive dynamic quantitative relationship between plasma, blood, and lung tissue concentration using the population pharmacokinetic modeling method, seventeen cynomolgus macaques were divided into six groups according to different HCQ dosing regimens over 5 days. The monkeys were euthanized, and blood, plasma, urine, feces and ten tissues were collected. All the samples were prepared by protein precipitation and analyzed by HPLC-MS/MS detection. The population pharmacokinetics of HCQ in the plasma, red blood cells, and lung tissue was conducted and simulated via ADAPT program. Results demonstrated that the maximum concentration (Cmax) of HCQ was 292.33 ng/mL in blood and 36.90 ng/mL in plasma after single dose of 3 mg/kg. The value of area under curve (AUC0-∞) was determined as 5,978.94 and 363.31 h* ng/mL for the blood and plasma, respectively. The descending order of the tissue-to-plasma concentration ratio was liver > spleen > kidney > lung > heart > subcutaneous fat > brain. The tissue-to-plasma concentration ratio and the tissue-to-blood concentration ratio for lung were found to be time-dependent with 267.38 and 5.55 at 120 h postdose, respectively. A five-compartment model with first-order oral absorption and elimination best described the plasma, blood, and lung tissue pharmacokinetics. The estimated elimination rate constant (ke) for a typical monkey was 0.236 h−1. The volume of distribution in central (Vc/F) and other two peripheral compartments (Vb/F and Vl/F) were 114, 2.68, and 5.55 L, respectively. Model-based simulation with PK parameters from cynomolgus macaques showed that the ratio of the blood or plasma to lung tissue was a dynamic change course, which suggested that the rate of HCQ concentration decrease in the blood or plasma was faster than that in the lung tissue. HCQ was found to be accumulated in tissues, especially in the liver, kidney, lung, and spleen. Also, the tissue-to-plasma concentration ratio increased over time. The population pharmacokinetic model developed could allow for the assessment of pharmacokinetics-pharmacodynamics relationships, especially relevant tissue concentration-response for HCQ. Determining appropriate treatment regimens in animals allows translation of these to clinical studies.